PENGARUH UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSETS (ROA) TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI MAKANAN DAN MINUMAN - Indra Saputra; Mega Andani; Halimatus Sa'diah (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
This study aims to empirically prove the effect of company size, Debt to Equty Ratio (DER), and Return On Assets (ROA) on earnings management in manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange in 2019-2022. The analysis method used in this study is to use multiple linear regression analysis methods using the SPSS Version 26 software statistical analysis tool. The conclusion of this study is that partially company size has no effect on earnings management, Debt to Equity Ratio (DER) affects earnings management and Return On Assets (ROA) has no effect on earnings management. While simultaneously company size, Debt to Assets Ratio (DAR), and Return On Assets (ROA) effect on earnings management.